Structural Design and Simulation Analysis of a Kind of Multi-function Intelligent Wheelchair - Wang Shukun; Chen Hui; Huang Yude; Liu Wei (Jixie chuandong)
A multi-functional intelligent wheelchair based on ergonomics is designed for the needs of special care people. Through market research and social investigation,the intelligent wheelchair has the walking function,docking function,lifting function and other auxiliary functions,and the corresponding executing agency is designed. Based on CATIA software,a three-dimensional model of wheelchair is established,and ADAMS software is used to analyze the motion of the docking function module of the intelligent wheelchair,and the feasibility of the mechanism is judged. Through ANSYS software,the statics analysis is carried out for key parts and docking function modules of intelligent wheelchair,which meets stiffness and strength conditions. The prototype test shows that all the functions of the wheelchair are realized,and the maximum driving speed,the forward speed,the slope angle and the bearing capacity are all in accordance with the national standards,and meet the ergonomics.